El cerdo cimarrón (Sus scrofa, Suidae) en la Isla del Coco, Costa Rica: Escarbaduras, alteraciones al suelo y erosión - Sierra, Claudine (2001)
Feral pigs (Sus scrofa) are of the most damaging exotic vertebrates, specially on oceanic island nativecommunities. Feral pigs inhabit Cocos Island since 1793 and there are around 400-500 individuals. In order toquantify the impacts of the feral pigs at Cocos Island, I calculated the effect of the rooting activity and its influ-ence on the natural erosion. During one year I walked, monthly, 15 km on trails estimating rooted area by tran-sect and rooting recurrence. During eight months I compared erosion rates with and without rootings. I estimat-ed the annual rooting rate between 10 and 20 % of the total island surface. The rooted area was the only meas-ured variable which correlated with the soil erosion rate. The erosion rate without rootings was 23.6 kg/ha/yearand with rootings was 200.4 kg/ha/year (P < 0.01). The disturbances provoked by the rootings were not scatteredhomogeneously through the island. The rootings, together with the natural landslides, dominate the soil distur-bance pattern at Cocos Island. This study suggests that the presence of feral pigs produces more erosion than theone that would naturally occur without feral pigs at Cocos Island.